Age at Immigration to Canada and the Occurrence of Mood, Anxiety, and Substance Use Disorders. (April 2013) - Patterson, Beth; Kyu, Hmwe Hmwe; Georgiades, Katholiki
Objective: The process of migration and resettlement has been associated with increased risk for psychiatric illness. Our study sought to examine the association between age at immigration and risk for mood, anxiety, and substance use disorders (SUDs) among adult immigrants in Canada. Method: Data from the Canadian Community Health Survey: Mental Health and Well-Being, a cross-sectional study of psychiatric disorder conducted in 2002, was used to identify a representative sample of adult immigrants in Canada ( n = 4946). Logistic regression was used to examine the association between age at immigration (0 to 5 years, 6 to 17 years, and 18 years and older) and 12-month prevalence of mood and anxiety disorders, and SUDs. Results: Immigrants who arrived prior to age 6 years reported the highest risk for mood (OR 3.41; 95% CI 1.7 to 7.0) and anxiety disorders (OR 6.89; 95% CI 3.5 to 13.5), compared with those who immigrated at the age of 18 years or older, after adjusting for covariates, including duration of residence. Conclusions: Younger age at immigration was associated with increased risk of having a current mood disorder, anxiety disorder, or SUD. These findings speak to the importance of developing and evaluating targeted prevention programs for young immigrant children and adolescents.